(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: Loyalty programs are widely used by businesses to influence consumer purchasing behavior and build long-term relationships with customers. In a competitive market like Kathmandu Valley, understanding how loyalty programs affect customer satisfaction and loyalty is essential for businesses to retain consumers and enhance buying behavior. Purpose: The purpose of this study is to assess the effectiveness of loyalty programs on consumers’ buying behavior in Kathmandu Valley. Design/Methodology/Approach: This study adopts an explanatory research design and uses a convenience sampling method. Data was collected through structured questionnaires from 403 respondents residing in Kathmandu Valley using the KOBO Toolbox. The study applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the effectiveness of loyalty programs on consumers’ buying behavior. Findings: The results reveal that loyalty programs significantly influence customer satisfaction and customer loyalty. Satisfaction also has a significant positive impact on customer loyalty. Furthermore, mediation analysis confirms that satisfaction significantly mediates the relationship between loyalty programs and customer loyalty. Conclusion: The study concludes that loyalty programs play a significant role in shaping consumers’ buying behavior by enhancing customer satisfaction and loyalty. Well-designed and innovative loyalty programs are essential for building long-term customer relationships and improving business performance. Keywords: Loyalty Programs, Customer Satisfaction, Customer Loyalty, Partial Least Square Structural Equation Modeling, Buying Behavior